Hygiene and sanitation practices in school children: an evaluation of WASH conditions in Visakhapatnam - Payala Vijayalakshmi; M. Kiranmai Reddy; K. V. Santhee Devi; Indugula Jyothi Padmaja (Journal of Water, Sanitation and Hygiene for Development, 2023)
The three autonomous factors of public health concern are WASH, constituting water, sanitation, and hygiene. The availability of WASH facilities at schools is a little-researched aspect that might be a crucial enabler of academic success. The present study was carried out to evaluate the hygiene and sanitation practices like right-hand washing with soap (RHWWS), right tooth brushing twice a day (RTBTD), and open defecation (OD) free among the school children of Visakhapatnam of 6–11 years of age. About 110 schools were identified, which includes 56 urban, 21 semi-urban, and 33 rural schools in the Visakhapatnam district, from which 500 students were selected randomly. Only 31 (28%) schools were exposed to WASH-related involvements. In the studied schools, only 58% of them have adopted the WASH policy. The results relating to the hygiene practices among the selected schools were found to be significant but, overall, a bit low on criteria defined by the UN joint monitoring program in 2018. To our knowledge, this is the first study to use a cross-sectional trail to test the impact of school WASH facilities and practices among primary school children in Visakhapatnam. The results concluded that the proper sanitation and hygiene practices are required for school children. HIGHLIGHTS To our knowledge, this is the first study to use a cross-sectional trial to test the impact of school WASH facilities and practices among primary school children in Visakhapatnam.; The present study took into consideration three different regions of schools.; The present study is an initial attempt to start filling a gap in the holistic assessment of school children's hygiene practices in Andhra Pradesh.;